STRATEGI PRODUK KAJIAN AFTERWORK MASJID AL LATHIIF BANDUNG - Syauqi, Rasyid Ilyasa (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2023)
Masjid Al Lathiif in Bandung is actively involved in religious and educational activities. The regular program called